A5_8 A Great Punch Line - Penney, Jordan; Allison, Hayley Jane; Leyser, Roger Paul; Lipscombe, Giles Christopher (Physics Special Topics, 2014)
Leicester University has a prodigious history with its Karate Club and this paper investigates the total force transferred in a Karate punch and the mass limit needed for a person to be able to break wood with such a technique. The results show that the mass needed to overcome the Ultimate Tensile strength of wood is 104 kg.